Nahum Situmorang dan Amir Pasaribu: Seniman Legendaris dari Tanah Batak dan Kontribusi terhadap Perkembangan Musik Indonesia - Flores Tanjung; Abdul Haris Nasution; Lister Eva Simangunsong (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
This study aims to find out the artists who came from the Batak Land during the Dutch colonial period in Indonesia, the independence period, and the post-independence period, as well as the specialty of the artists in motivating the workers in the millennial era or the present. The research method used is descriptive qualitative with a historical approach through heuristic steps (collection of data relevant to the topic of study, both primary and secondary), for verification (criticism of external and internal sources), for further interpretation. The analysis was carried out using the theory of semiotics (Ferdinand De Saussure), namely content analysis. The results show that North Sumatra, especially the Tapanuli region, is the hometown for many artists, especially musicians with various genres known at the national and international level. The strength of the lyrics and musicality from the traditional to the popular modern has strengthened the variety of themes and musical compositions so that they become part of the atmosphere that supports the emergence of